PILOT STUDY ON THE IMPACT OF FINANCIAL LITERACY PROGRAMS ON SAVINGS BEHAVIOUR AMONG RURAL WOMEN IN PUNE DISTRICT - Khedkar, Gayatri Shankar; Lande, Ganesh Sambhaji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the rural women’s financial awareness regarding their investment. It studies the influence of financial awareness on rural women’s saving behaviour in Pune district. Indian government giving push towards the women empowerment and their financial inclusion hence it is important to understand the awareness extent of financial investment among the women’s especially in rural areas. From primary data comprising 50 rural women, the awareness levels, preferences, and change in behaviour post-literacy intervention are analysed in this study. For testing the hypotheses concerning financial awareness, influence of demographics, and investment behaviour, it was decided that statistical tools such as the T-test and Chi-square test would be used. The research findings establish that financial literacy inculcates discipline to save, trusts-institution, awareness for investing avenues for rural women. Therefore, the study concludes that continuous and targeted financial literacy training in the long term will surely maximize the financial independence and economic participation of rural women.